2005
DOI: 10.1111/j.1744-7410.2005.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

First record of Polymerurus (Gastrotricha, Chaetonotida) from Australia with the description of a new species from Queensland and of cuticular ultrastructure in P. nodicaudus

Abstract: Abstract. Identification of specimens in the genus Polymerurus (Gastrotricha, Chaetonotida) is reported for the first time from Australia. The genus includes 3 species from a freshwater lake in southern Queensland. Two species, Polymerurus rhomboides and P. nodicaudus, are well-known cosmopolitans: P. rhomboides is now known from every continent except Antarctica, and P. nodicaudus from all continents except Africa and Antarctica. An ultrastructural description of the cuticle in P. nodicaudus is provided and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…), with the possible exception of the stalked scales that make up the cuticular armature of this animals; a trait shared with many members of the more basal Xenotrichulidae (but also with Polymerurus rhomboides ). So far, however, there is little evidence to confirm the homology of these two cuticular structures (see Hochberg 2005b) but the molecular data suggest a closer examination is required.…”
Section: Discussionmentioning
confidence: 99%
“…), with the possible exception of the stalked scales that make up the cuticular armature of this animals; a trait shared with many members of the more basal Xenotrichulidae (but also with Polymerurus rhomboides ). So far, however, there is little evidence to confirm the homology of these two cuticular structures (see Hochberg 2005b) but the molecular data suggest a closer examination is required.…”
Section: Discussionmentioning
confidence: 99%
“…This species is widely distributed in Europe (see e. g. Marcolongo 1910;1914;Mola 1932;Valkanov 1937;Rudescu 1967;Martin 1981;Schwank 1990;Kisielewski 1998) and is also reported from Israel (Kisielewski 1999), Japan (Saito 1937), Korea (Lee & Chang 2000); Cameroon (Togouet Zébaz et al 2007), Canada (Schwank 1990), United States (Stokes 1887;Davison 1938;Anderson & Robbins 1980), Argentina (Grosso 1975;Grosso & Drahg 1983), Brazil (Kisielewski 1991) and Australia (Hochberg 2005).…”
Section: Genus Polymerurus Remane 1927mentioning
confidence: 90%
“…This species is widely distributed in Europe (see e. g. Marcolongo 1910;Valkanov 1937;Rudescu 1967;Martin 1981;Schwank 1990;Kisielewski 1998) and is also reported from India (Naidu & Rao 2004), Israel (Kisielewski 1999), Japan (Saito 1937;Sudzuki 1975), Korea (Lee & Chang 2000), Canada (Schwank 1990), United States (Bryce 1924;Davison 1938), Brazil (Kisielewski 1991) and Australia (Hochberg 2005). Localities.…”
Section: Genus Polymerurus Remane 1927mentioning
confidence: 99%
“…Aspidiophorus is a group traditionally diagnosed by the presence of pedunculated scales, a trait also found within Neogosseidae, Xenotrichulidae and among Chaetonotidae in Polymerurus (see e.g. Hochberg 2005;Ruppert 1979;Todaro et al 2013). Furthermore, recent molecular studies (Kånneby et al 2013) have indicated that the group is nonmonophyletic and it appears that marine members of the group are the sister group of all other Chaetonotidae and Dasydytidae; clear indications for future investigations on these little creatures.…”
Section: Taxonomic Remarksmentioning
confidence: 95%